Affective norms for 501 Chinese words from three emotional dimensions rated by depressive disorder patients - Xu, Xinyue; An, Fei; Wu, Shengjun; Wang, Hui; Kang, Qi; Wang, Ying; Zhu, Ting; Zhang, Bing; Huang, Wei; Liu, Xufeng; Wang, Xiuchao (Frontiers in Psychiatry, 2024)
Emotional words are often used as stimulus material to explore the cognitive and emotional characteristics of individuals with depressive disorder, while normal individuals mostly rate the scores of affective words. Given that individuals with depressive disorder exhibit a negative cognitive bias, it is possible that their depressive state could influence the ratings of affective words. To enhance the validity of the stimulus material, we specifically recruited patients with depression to provide these ratings. This study provided subjective ratings for 501 Chinese affective norms, incorporating 167 negative words selected from depressive disorder patients’ Sino Weibo blogs, and 167 neutral words and 167 positive words selected from the Chinese Affective Word System (Wang, Zhou, & Luo, 2008). The norms are based on the assessments made by 91 patients with depressive disorder and 92 normal individuals, by using the paper-and-pencil quiz on a 9-point scale. Regardless of the group, the results show high reliability and validity. We identified group differences in three dimensions: valence, arousal, and self-relevance: the depression group rated negative words higher, but positive and neutral words lower than the normal control group. The emotional perception affected the individual’s perception of words, to some extent, this database expanded the ratings and provided a reference for exploring norms for individuals with different emotional states.